The Impact of Educational Management Information System (EMIS) on University Leadership and Management: The Case of the University of Bamenda, Cameroon - Emile Monono Mbua (Researchparks Publishing, 2022)
Information is key ingredient in effective education system. This study aimed at investigating the impact of EMIS on leadership and management in the University of Bamenda. Specifically, it identified EMIS services, major problems and challenges of EMIS implementation and utilization by students, lecturers and administrative staff as well as the impact of EMIS on leadership and management in the University of Bamenda. Review of literature was done on the meaning of EMIS, Major problems and challenges facing leaders and managers in the use of EMIS and the impact of EMIS on leadership and management. Questionnaires and observation were used to collect information from the respondents. Tables and percentage were used to describe the data obtained. It was found that the university is inadequately equipped with EMIS operations. The study recommends some awareness creations at all the levels through workshops, seminars, written materials and other related methods.